Irregular sleep and cardiometabolic risk: Clinical evidence and mechanisms - Zhang, Chengjie; Qin, Gang (Frontiers in Cardiovascular Medicine, 2023)
Sleep regularity is an essential feature of sleep. Shocked by the modern lifestyle, irregular sleep is widespread in the population. Studies have explored the relationship between sleep regularity and cardiometabolic disease, but the results are inconsistent. Meanwhile, the heterogeneity between studies is considerable. There is a lack of further integration to clarify the relationship between them. The paper synthesizes evidence from current clinical studies to summarize the measures of sleep regularity in the existing literature and discuss the role of different sleep regularity indicators in the occurrence and development of cardiovascular and metabolic diseases (coronary heart disease, hypertension, obesity, and diabetes). Furthermore, the relevant literature was reviewed to generalize the potential mechanism through which irregular sleep increases cardiometabolic risk, including circadian dysfunction, inflammation, autonomic dysfunction, HPA axis disorder, and gut dysbiosis. Health-related practitioners should give more attention to the role of sleep regularity on human cardiometabolic in the future.